Electrical unit and associated additional functional module (2017)
The subject matter of the present invention is an electrical unit for an electrical installation that is capable of and intended for being connected to an electrical network, comprising at least: a primary functional module that is capable of and intended for performing a current-switching function; an additional functional module for performing at least one function requiring an electrical power supply, which electrical unit is characterized in that the function of the additional functional module is a function requiring an electrical power supply with the exception of a lighting function.